The Relationship Between Workload and Job Stress among Human Resources Personnel at the Police Academy - Geia Aisya Kusumawati; Laily Rahmah (UIN Sultan Aji Muhammad Idris Samarinda, 2026)
Workload is one of the major organizational factors that may contribute to job stress among employees. Human Resources personnel at the Police Academy are responsible for various administrative functions requiring accuracy, responsibility, and adherence to strict deadlines, which may increase their vulnerability to job stress. This study aimed to examine the relationship between workload and job stress among Human Resources personnel at the Police Academy and to identify whether there were differences in job stress based on gender. This study employed a quantitative correlational design involving 143 personnel of the Human Resources Division of the Police Academy. Data were collected using the Workload Scale and the Job Stress Scale, each consisting of 24 valid items. Reliability testing indicated excellent internal consistency, with Cronbach’s Alpha coefficients of 0.971 for the Workload Scale and 0.977 for the Job Stress Scale. Data analysis was conducted using Spearman’s rank-order correlation and the Mann–Whitney U test. The results revealed a significant positive relationship between workload and job stress (rs = 0.860, p < 0.05), indicating that higher workload was associated with higher levels of job stress among Human Resources personnel at the Police Academy. These findings were supported by preliminary survey results indicating that accumulated tasks, administrative demands, time pressure, and overtime work contributed to job stress, which was reflected in physical fatigue, psychological strain, and behavioral changes among personnel. Furthermore, the Mann–Whitney U test indicated no significant difference in job stress between male and female personnel (U = 2317.000, p = 0.720; p > 0.05). These findings suggest that workload is an important determinant of job stress among Human Resources personnel at the Police Academy. Effective workload management and organizational support are therefore essential to maintain employee well-being and reduce occupational stress.